THE EFFECT OF INFORMATION TECHNOLOGY ON COMMUNITY HEALTH CENTER PERFORMANCE THROUGH ENGAGEMENT MANAGEMENT AS AN INTERVENING VARIABLE - Yudyarto, Koeshar; Satoto, Eko Budi; Sanosra, Abadi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The aim of this research is to analyze the effect of information technology on engagement management, analyze the effect of information technology on organizational performance, analyze the effect of engagement management on organizational performance, and analyze the effect of information technology on organizational performance through engagement management as an intervention. Method: This research uses descriptive and quantitative research methods. The population was all BLUD Health Centers in Jember Regency, totaling 50 Community Health Centers. The sample was the Head and the Person in Charge of Personnel at the BLUD Community Health Center in Jember Regency and was taken by total sampling, so that the total sample in this study was 100 respondents. Data processing in this research uses Variance-based SEM or Partial Least Square (SEM-PLS) with the Warp-PLS 7.0 SEM PLS program. Results: Research findings state that there is a positive and significant effect of information technology on engagement management. There is a positive and significant effect of information technology on organizational performance. There is a positive and significant effect of engagement management on organizational performance. There is a positive and significant effect of information technology on organizational performance through engagement management as an intervening variable. Novelty: This research uses a model of factors that effect organizational performance by involving information technology and engagement management (as an intervening).